PENGEMBANGAN PROFESSIONAL KEGURUAN DALAM MATA KULIAH MICRO TEACHING - Mashuri Mashuri (Jurnal Ilmiah Didaktika, 2012)
The quality of education is really determined by various factors, but the most dominant and important is a teacher's professionalism. Almost all effort on curriculum reform and teaching method implementation, is depends on the teachers ultimately. Any teachers lack of ability of the teaching material, teaching strategy, motivate the students to achieve high perpformance, will not improve the quality of education. The teacher acts as one crucial component in educational system. Therefore, since at the very the beginning, the ability of micro teaching practice at a college should be prepared well in order to be a professional teacher in the future. In the modern education system, teacher candidates are required to have professional skills that include the ability to plan learning, learning implementation, and learning evaluation. Without mastering all these aspects, the teacher will not be able to achieve the learning objectives optimally.